Benzocyclobutene polymer in glass multimode interference thermo-optic switch - Yaacob, Maslina (2010)
Optical switch fabrics are integral parts of optically switched network because these devices are capable to direct input traffic to the appropriate output interface without resorting to optical-to-electrical-to-optical (OEO) conversion. This thesis is significantly devoted towards the design and simulation work of optical switch based on 2×2 multimode interference (MMI) coupler and exploiting thermo-optical properties of materials. Photosensitive BenzoCyclobutene (BCB 4024-40) polymer based coupler material was chosen due to its high thermo-optic coefficient, which offers less power consumption to induce thermo-optic effect in MMI coupler. The switching of the input signal to the desired output ports are realized by modifying refractive index at particular section of MMI coupler. Light propagation and thermal distribution through the optical switch are modeled by using a Finite Difference Beam Propagation Method (FD-BPM). In order to reduce the switching power, further analysis has been done by exploring the effect of heater’s geometrical structure. It was observed that the employment of trapezoidal (tapered) heater structure can reduce the applied switching power by 15.53% as compared to the conventional rectangular structure. This improvement was shown to take place at crosstalk value of -19 dB. Significantly, this research has successfully demonstrated the application of tapered heater electrode in reducing the switching power for thermo-optic switch application.